2022
DOI: 10.21037/atm-22-3560
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and verification of a nomogram for predicting survival in patients with triple-positive breast cancer

Abstract: Background: Triple-positive breast cancer (TPBC) is a specific type of breast cancer characterized by the positive expression of estrogen receptor (ER)/progesterone receptor (PR)/human epidermal growth factor receptor 2 (HER-2). In recent years, the research on breast cancer has been increasing year by year, but there are few studies on TPBC, especially the lack of analysis with large sample size. In this study, sufficient samples were provided through the SEER database, explore the factors affecting the progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Currently, TNM prognostic staging is commonly used to assess the prognosis of breast cancer patients. In this study, patients had a worse prognosis as the TNM stage increased, which is consistent with previous studies ( 27 ). Breast-conserving therapy (BCT) had similar long-term survival outcomes to mastectomy in patients with early breast cancer, and recent studies had reported similar rates of recurrence compared with mastectomy ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Currently, TNM prognostic staging is commonly used to assess the prognosis of breast cancer patients. In this study, patients had a worse prognosis as the TNM stage increased, which is consistent with previous studies ( 27 ). Breast-conserving therapy (BCT) had similar long-term survival outcomes to mastectomy in patients with early breast cancer, and recent studies had reported similar rates of recurrence compared with mastectomy ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although other researchers have done similar work ( 27 ), Compared with previous studies, the innovations of this study are as follows. Firstly, by including a Chinese cohort, the variability of clinical characteristics of TPBC patients by race was explored.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms are digital graphical tools with the integration of several key variables, which are now commonly applied for event prediction, especially for prognosis prediction in cancers. Compared to the traditional TNM stage, it can include more tumor characteristics and has gained extensive usage in forecasting the outcomes of various cancer types (8)(9)(10). Several nomograms have been established for prognosis prediction, lymph node metastasis prediction, or distant metastasis prediction in GBC (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%